A Clinical Approach to Intrahepatic Cholestasis of Pregnancy - Diken, Zaid; Usta, Ihab M.; Nassar, Anwar H. (American Journal of Perinatology, 2014)
Intrahepatic cholestasis of pregnancy (ICP) has a varying prevalence worldwide. The etiology behind this disease remains not fully understood with multiple factors influencing its development including genetic variations, dietary factors, hormonal changes, and environmental influences. Presenting mainly during the third trimester with generalized itching and resolving spontaneously postpartum, this condition is still associated with fetal morbidity and mortality. The diagnosis is based on clinical presentation in association with biochemical abnormalities. Elevation in total bile acid levels is the most frequent laboratory abnormality and seems to be the most important for gauging further management of the disease. The most appropriate gestational age for the delivery of women with ICP is yet to be determined. In this review we discuss the epidemiology, clinical features, diagnosis, etiology, and management of ICP, trying to shed light on some controversial aspects of the disease.
Keywords: intrahepatic cholestasis of pregnancy; epidemiology; etiology; diagnosis; management